Automatic power factor correction using a modified statcom as a continuously controlled capacitive static VAR compensator - Obais A.M.; Pasupuleti J. (Praise Worthy Prize S.r.l, 2023)
In this paper an automatic power factor correction system based on a new vision to statcom concept is presented. The reactive component of the load current is supplied by a statcom built of a halt-bridge voltage source inverter feeding a reactor and shunted by two dc capacitors. The passive components and control scheme of this configuration are approached in such a manner that the devised statcom behaves as pure capacitive impedance. The control strategy is based on governing the statcom current by its modulation index, while the passive components are designed such that all harmonic current harmonics are suppressed by the statcom reactor. The modulation index is controlled linearly by a precision gain-controlled linear amplifier which is specifically designed for this compensator and directly controlled by the load reactive current component. Modeling and performance of the proposed system was verified on PSpice. 2012 Praise Worthy Prize S.r.l. - All rights reserved.